Spermatogonial Stem Cell Markers and Niche in Equids - Costa, Guilherme M. J. (Public Library of Science, 2012)
Spermatogonial stem cells (SSCs) are the foundation of spermatogenesis and are located in a highly dynamic microenvironment called “niche” that influences all aspects of stem cell function, including homing, self-renewal and differentiation. Several studies have recently identified specific proteins that regulate the fate of SSCs. These studies also aimed at identifying surface markers that would facilitate the isolation of these cells in different vertebrate species. The present study is the first to investigate SSC physiology and niche in stallions and to offer a comparative evaluation of undifferentiated type A spermatogonia (Aund) markers (GFRA1, PLZF and CSF1R) in three different domestic equid species (stallions, donkeys, and mules). Aund were first characterized according to their morphology and expression of the GFRA1 receptor. Our findings strongly suggest that in stallions these cells were preferentially located in the areas facing the interstitium, particularly those nearby blood vessels. This distribution is similar to what has been observed in other vertebrate species. In addition, all three Aund markers were expressed in the equid species evaluated in this study. These markers have been well characterized in other mammalian species, which suggests that the molecular mechanisms that maintain the niche and Aund/SSCs physiology are conserved among mammals. We hope that our findings will help future studies needing isolation and cryopreservation of equids SSCs. In addition, our data will be very useful for studies that aim at preserving the germplasm of valuable animals, and involve germ cell transplantation or xenografts of equids testis fragments/germ cells suspensions.